Niepodległość . pismo Liberalno-Demokratycznej Partii "Niepodległość", no. 4, 1986 - Spudych, Barbara (s.n.], 1986)
Creation and circulation: Issues no. 1-2(1985) and 3(1986) published as a separate edition by Antyk Press.